Impacts of Public Relations on Corporate Reputation - Jing Wun Lee (Journal of Digital Marketing and Communication, 2022)
This article reviews the impact of public relations on corporate reputation in the contemporary corporate environment. A favorable reputation enables businesses to maintain a competitive advantage. In order to achieve long-term success, it is essential for businesses to establish and preserve a positive reputation. This report used real-world examples to illustrate how effective communication aids in reputation management. In addition, this essay is dependent on conjectures and an interview with an experienced Public Relations practitioner. Nonetheless, there are a number of ways for firms to communicate with their stakeholders more effectively in order to develop a positive corporate reputation. Most crucially, firms require Public Relations professionals to aid in establishing and maintaining connections with various stakeholder groups. Consequently, it is essential for firms to identify and comprehend their key stakeholders, as well as employ effective communication tactics, in order to maintain a positive reputation.